Peran Tenaga Kesehatan dalam Penanggulangan Banjir di Pasuruan pada Bulan Februari Tahun 2023 - Silvia Rahmawati Permata Koriyah; Satriya Wijaya; Didiek Rachmadi (Yayasan Literasi Sains Indonesia, 2023)
Disaster preparation is a step towards disaster risk reduction. Disaster risk reduction can be in the form of disaster management plans, early warning systems, evacuation sites and provision of essential goods. According to PERMENKES No. 66 of 2016, which is a guideline for health HR management in disaster management, the crisis response team includes the Rapid Reaction Team (TRC), Rapid Assessment Team (TPC/RHA team) and Health Assistance Team. The purpose of this research is to evaluate material in terms of preparedness policies and human resources when facing disasters. The type of research used is descriptive quantitative. Pasuruan Regency and Pasuruan City experienced floods 7 times during the month of February. A total of 2,520 residents were affected by the flood disaster. The need for health human resources for TRC among residents/refugees between 10,000-20,000 such as general practitioners and specialists, nurses, epidemiological surveillance, pharmacists, nutritionists, midwives communication officers, ambulance drivers, and DVI personnel. With the existence of regulations/policies that have been set, it really helps to facilitate the performance of health human resources in handling disaster-affected residents to the fullest. The role of health workers and disaster preparedness is very important. It is suggested that with this research, health human resources are expected to always increase their competence and increase their role so that when they go down to help residents affected by a disaster, they already have strong enough potential to be implemented to residents.